The Imact of Capital, Concentration, Size and Liquidity on Banking Industry Performance in Nigeria - Obilikwu, James (International Journal of Economics and Financial Issues, 2018)
This paper investigates the impact of bank’s consolidation targeted variables (capital adequacy, concentration, bank-size and liquidity) in conjunction with economic growth and inflation on the industry’s performance in Nigeria. Data from 1980 – 2010 were used for the assessment, and were sourced from Central Bank of Nigeria (CBN), Nigerian Deposit Insurance Cooperation (NDIC) and Annual Reports of the banks. Vector Error Correction Model (VECM) was used for the examination. Findings reveal that contrary to the expectation of the consolidation policy, concentration, bank-size and liquidity negatively impacted the industry. It was only capital adequacy that exerted positive impact on the performance. Based on the findings, the consolidation targeted variables as there were should have been relied upon solely as the means of improving the performance of the Nigerian banking industry. Consequently, it is recommended that the regulatory authority; CBN should constantly ensure that banks maintained regulated capital adequacy ratio. The industry should not further be concentrated; banks should be categorized into different sizes and be allowed to choose any category they can efficiently manage depending on their capacity, experience, and mode of operation. The banks should improve on their long term deposits mobilization as a vital source of meeting their liquidity needs and should design financial products that meet the needs of all income groups for more all-inclusive banking and economy that will positively impact the banks. Keywords: Impact, Consolidation targeted variables, Bank performance, VECM, JEL Classifications: G21, G34, G38